Use of Silica Fume and GGBS to Improve Frost Resistance of ECC with High-Volume Fly Ash - Yushi Liu; Xiaoming Zhou; Chengbo Lv; Yingzi Yang; Tianan Liu (Advances in Civil Engineering)
Fly ash (FA) has been an important ingredient for engineered cementitious composite (ECC) with excellent tensile strain capacity and multiple cracking. Unfortunately, the frost resistance of ECC with high-volume FA has always been a problem. This paper discusses the influence of silica fume (SF) and ground-granulated blast-furnace slag (GGBS) on the frost resistance of ECC with high volume of FA. Four ECC mixtures, ECC (50% FA), ECC (70% FA), ECC (30% FA + 40% SL), and ECC (65% FA + 5% SF), are evaluated by freezing-thawing cycles up to 200 cycles in tap water and sodium chloride solution. The result shows the relative dynamic elastic modulus and mass loss of ECC in sodium chloride solution by freeze-thaw cycles are larger than those in tap water by freeze-thaw cycles. Moreover, the relative dynamic elastic modulus and mass loss of ECC by freeze-thaw cycles increase with FA content increasing. However, the ECC (30% FA + 40% SL) shows a lower relative dynamic elastic modulus and mass loss, but its deflection upon four-point bending test is relatively smaller before and after freeze-thaw cycles. By contrast, the ECC (65% FA + 5% SF) exhibits a significant deflection increase with higher first cracking load, and the toughness increases sharply after freeze-thaw cycles, meaning ECC has good toughness property.